Carbonates mineralogy and chemistry - Reeder, Richard J. (Reviews in mineralogy ;, 2019)
Volume 11 of Reviews in Mineralogy attempts to synthesize our present understanding of certain aspects of the mineralogy and chemistry of the rock-forming carbonates. This review follows, by ten years, a major assessment of (sedimentary) carbonate minerals by Lippmann (1973). There is only minor overlap of subject material, and I hope that this difference reflects fairly how this field has developed.In this volume, some of the papers are general (i.e., those addressing crystal chemistry and phase relations), and they provide overviews of a fundamental nature and are of interest to many. Others are more specialized in coverage and generally reflect the different approaches used in carbonate geochemistry. The final chapter introduces transmission electron microscopy, a relatively new and powerful technique for mineralogical research that has great potential in carbonate research.